Design and Development of an Automatic Lock System for Cupboards Using Fingerprint Based Microcontrollers - Afni Mardhiyah; Siswanto (Journal of Technology Informatics and Engineering, 2023)
: Seeing the current condition of the community, most of them still use simple security, such as the cupboard security system at Weleri Muhammadiyah 3 Vocational School, the situation is that schools still use one key in one cabinet where only one person is employed while more than one TU officer is if other officers will use the cupboard, they must look for or wait for the key holder first and the method is not effective for emergency matters. The importance of making security in the closet is because the school is the school with the highest number of students and requires safe storage media for diplomas (not yet taken). Therefore, it is necessary to make a cabinet lock application system using microcontroller-based fingerprints. This cabinet lock system uses a fingerprint scanner as the main determinant of whether the cabinet can be opened automatically. From research at Weleri Muhammadiyah 3 Vocational School, this system was able to add a security system to the cabinet to control access rights in the cabinets that were considered important.